Distribution and Seasonality of the Omura’s Whale (Balaenoptera omurai) in Australia Based on Passive Acoustic Recordings - Ciara Edan Browne; Christine Erbe; Robert D. McCauley (Animals, 2024)
The Omura’s whale (Balaenoptera omurai) is one of the most recently described species of baleen whale. Initially known only from stranding and whaling specimens, it has now been identified in all ocean basins excluding the central and eastern Pacific. Unlike most baleen whales that migrate between the poles and the equator seasonally, the Omura’s whale is known to inhabit tropical to sub-tropical waters year-round. In Australian waters, there remain fewer than 30 confirmed visual sightings over the past decade. However, based on acoustic records, the Omura’s whale has been detected off areas of the northwest coast of Australia year-round. This study utilises passive acoustic recordings from 41 locations around Australia from 2005 to 2023 to assess the distribution and seasonality of the Omura’s whale. The seasonal presence of Omura’s whale vocalisations varied by location, with higher presence at lower latitudes. Vocalisations were detected year-round in the Joseph Bonaparte Gulf in the Timor Sea, and near Browse Island and Scott Reef, in the Kimberley region. In the Pilbara region, acoustic presence mostly peaked from February to April and no acoustic presence was consistently observed from July to September across all sites. The most southerly occurrence of Omura’s whale vocalisations was recorded off the North West Cape in the Gascoyne region. Vocalisations similar but not identical to those of the Omura’s whale were detected in the Great Barrier Reef. The identified seasonal distribution provides valuable information to assess environmental and anthropogenic pressures on the Omura’s whale and to aid in creating management and conservation policies for the species in Australia.